2019
DOI: 10.1186/s12967-019-1767-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-regulated pathways of flow-stimulated angiogenesis and vascular remodeling in vivo

Abstract: BackgroundVascular shear stress promotes endothelial cell sprouting in vitro. The impact of hemodynamic forces on microRNA (miRNA) and gene expression within growing vascular networks in vivo, however, remain poorly investigated. Arteriovenous (AV) shunts are an established model for induction of neoangiogenesis in vivo and can serve as a tool for analysis of hemodynamic effects on miRNA and gene expression profiles over time.MethodsAV shunts were microsurgically created in rats and explanted on postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…The relative abundance level for each miRNA was calculated using the 2 −ΔΔCT equation [23]. RNU6B small nuclear RNA (snRNA) was used an endogenous reference control for normalization purpose as previously described [12,13,22,[24][25][26][27] and because of its minimum abundance variance between the TS patients and HVs as observed by DataAssist™Software (Applied Biosystems). Correlations were computed using Spearman's regression coefficient and the difference between the groups was analyzed using a Mann-Whitney-U test using GraphPad Prism 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…The relative abundance level for each miRNA was calculated using the 2 −ΔΔCT equation [23]. RNU6B small nuclear RNA (snRNA) was used an endogenous reference control for normalization purpose as previously described [12,13,22,[24][25][26][27] and because of its minimum abundance variance between the TS patients and HVs as observed by DataAssist™Software (Applied Biosystems). Correlations were computed using Spearman's regression coefficient and the difference between the groups was analyzed using a Mann-Whitney-U test using GraphPad Prism 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-124 plays a key role in multiple diseases including IPF by targeting SMAD5, CAV1, JAG1, ROCK1 or STAT3 [37][38][39][40][41][42], which is consistent with our findings. Previous studies have also shown that FOXC1 and HSPA1A are direct target genes of miR-223 [43,44], and these genes contribute to the pathogenesis of IPF via activating various signaling pathways. Our present results suggested that down-regulated hsa_circ_0029633 might promote the development of IPF by increasing the expression of miR-223, and further decreasing the expression of FOXC1 and HSPA1A.…”
Section: Discussionmentioning
confidence: 95%
“…CXCL2 was involved in various biological progresses, such as angiogenesis, inflammation and cancer biological behaviors (23,(27)(28)(29)(30). CXCL2 was also considered to be a proinflammatory factor in RA (24).…”
Section: Discussionmentioning
confidence: 99%